Studying of Eloquent and Rhetorical Errors in Mirzadeh Eshghi's Poems - علی سلیمانی; محمود بشیری (مطالعات زبانی و بلاغی)
The most literary critics confirm that the poetic language of Mashrooteh movement is the ordinary one, in spite of its new themes and poetic creativities. Therby, its ordinary language causes the eloquent errors which are opposite of the Persian language standards. Mirzadeh Eshghi is one of those poets who made the mentioned errors. On controry of the prior studies which looks at it generrally, this research involves the studying of eloquent errors in Eshghi's poem specifically. Therefore we understand that, in the level of word, analogy and barbarism are great errors in Mirzadeh Eshghi's poem so that it leads to cacophony. In level of sentence, also, solecism is the prevalent error in his poet. The  usage of other   eloquent errors are less than the mentioned ones.